AGE-OLD, SEXUAL AND SOMATOTYPOLOGICAL FEATURE OF SENTINEL INDEXES OF RHEOVASOGRAPHY OF SHIN FOR PRACTICALLY HEALTHY YOUTHS AND GIRLS OF PODILLYA - Ivanitsa, A.O. (World of Medicine and Biology, 2014)
The aim of this research was establishment of age-old, sexual and somatotypological features of sentinel indexes of shin rheovasography for practically healthy municipal youths and girls of Podolie. As a result of undertaken studies the set limits of confidence intervals and percentile scope of sentinel indexes of shin rheovasography are in general, different age-old and different after somatotype groups practically healthy youths and girls. In most cases age-old, sexual and somatotypological features of sentinel indexes of shin rheovasography both for youths and for girls touch time of descending part of rheovasography and time of the rapid blood filling.